2008
DOI: 10.1186/1472-6963-8-186
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in infertile couples receiving IVF or ICSI treatment

Abstract: Background: Infertile couples might experience psychological distress and suffer from impaired health-related quality of life. This study aimed to examine health-related quality of life in infertile couples receiving either in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
79
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 19 publications
15
79
5
4
Order By: Relevance
“…[43] Statistically, significant associations were found, in the present study, between infertility duration and degree of depression/anxiety/tension (p = .000, .000, .002), respectively. This result disagreed with the result of a study was done by Rashidi et al (2008) which found that mental quality of life has no relation to infertility duration. [51] Concerning the history of abortion, it was obvious from the results of the present study that 13.0% of the study subjects had previous aborted, 11.3% had aborted once only while only 1.8% had aborted twice or more.…”
Section: Published By Sciedu Presscontrasting
confidence: 56%
See 3 more Smart Citations
“…[43] Statistically, significant associations were found, in the present study, between infertility duration and degree of depression/anxiety/tension (p = .000, .000, .002), respectively. This result disagreed with the result of a study was done by Rashidi et al (2008) which found that mental quality of life has no relation to infertility duration. [51] Concerning the history of abortion, it was obvious from the results of the present study that 13.0% of the study subjects had previous aborted, 11.3% had aborted once only while only 1.8% had aborted twice or more.…”
Section: Published By Sciedu Presscontrasting
confidence: 56%
“…This result disagreed with the result of a study was done by Rashidi et al (2008) which found that mental quality of life has no relation to infertility duration. [51] Concerning the history of abortion, it was obvious from the results of the present study that 13.0% of the study subjects had previous aborted, 11.3% had aborted once only while only 1.8% had aborted twice or more. The previously aborted women had the lowest prevalence of depression, anxiety and tension when compared with the non-aborted ones (p = .000).…”
Section: Published By Sciedu Presscontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast, a study showed that long-term treatments in infertile couples caused better accept of their living conditions and hence increase the quality of life in older infertile couples 8 .…”
Section: Discussionmentioning
confidence: 97%